THE ROLE OF AJENGAN IN PESANTREN'S LEARNING SYSTEM - Solihin, Olih; Hkikmat, Mahi Mamat; Daniel, Yudi Irfan; Abdullah, Ahmad Zakki (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2024)
This study aims to analyze the learning system in Islamic boarding schools from the perspective of source credibility theory in building the authority of Ajengan. The research method employed is a qualitative approach with a case study conducted at Sirojul Huda Islamic Boarding School in Bandung Regency. Data were collected through in-depth interviews and participant observation. The findings indicate that the Ajengan's deep understanding of religious knowledge, expertise in delivering religious teachings, authority, and respectful communication style influence the students' perception of Ajengan's credibility as an authoritative communicator. The implications of this research highlight the importance of strengthening Ajengan's authority through the development of a learning system that emphasizes source credibility, interpersonal communication, and considers students' perceptions as learners. Keywords: learning system, Islamic boarding school, source credibility theory, Ajengan's authority, students' perception